Psychological Wellbeing and Impact of Traumatic Events on Frontline Health Service Staff Amid the Covid19 Pandemic - Murphy, Kevin Peter (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2025)
The aim of this research was to better understand the interplay of factors which influence psychological wellbeing, particularly those which have a potentially negative impact, and to explore support structures that mitigated these while frontline health staff worked within a traumatic environment. During the research, a double layer was occurring- health staff were working with trauma as part of their day-to-day professions, while at the same time they were experiencing a global trauma, the Covid19 pandemic. Precipitating this, there had been much written on experiences of frontline staff with respect to burnout, compassion fatigue, vicarious trauma and secondary traumatic stress. However it was often neglected to differentiate the nuances between these phenomena, which could potentially lead to the misconception they are interchangeable and benefit equally from the same support interventions. The current study sought to understand the extent these could be viewed more holistically as part of a person's comprehensive experience, as individual phenomena yet not in isolation from each other. In doing so, it was endeavoured to better understand the complex web which these weaved, and from this the impact the work environment can have on frontline healthcare staff. This consequently would allow for the creation of more accurate, appropriate and beneficial support structures. A mixed-methods approach was used combining quantitative psychometrics alongside qualitative interviews, across two timepoints 6 months apart. From this a rich tapestry of staff's wellbeing while working within an area of social deprivation during the Covid19 pandemic was unearthed. Significant results were found within elements of the study's exploration of compassion satisfaction, depression, burnout, and secondary traumatic stress. These results were then better understood when presented against the contextual backdrop of the qualitative interviews, which underwent a thematic analysis. From this, a visual matrix representation of supports was formed. Thus the study significantly informed greater in-depth awareness of the experiences of society's frontline defence against ill health, our health service staff. It is hoped that the matrix that was created can aid organisations to reciprocally maintain their staff's psychological health and wellbeing, thus reducing the impact that working in a traumatic environment can have on them.
APPROVED
Keywords: Pandemic; Covid19; Psychological wellbeing; Impact of traumatic events; frontline health service staff